Facile fabrication of porous NiCo2O4 nanosheets with high adsorption performance toward Congo red. (January 2019) - Bao, Yaqi; Qin, Ming; Yu, Yinkai; Zhang, Limin; Wu, Hongjing
Abstract: In this work, porous NiCo2 O4 nanosheets have been fabricated by a facile hydrothermal method. The morphology as well as crystalline structure of products was tested by XRD, FTIR, N2 adsorption-desorption isotherms and TEM. The composite exhibited excellent adsorptive removal capacity toward Congo red (CR), and the maximum adsorption capacity was up to 961.5 mg/g. The best adsorption performance was achieved in the CR solution without adjusting of pH. Adsorption accords with Langmuir isothermal adsorption model and the adsorption kinetic model is more in line with the pseudo-second order model. According to the adsorption mechanism investigation, adsorption was not caused by the electrostatic attractions but may be the formation of ionic bonding between metal ion in composite and -SO3 - in CR. The NiCo2 O4 nanosheets can be a good alternative for the high-performance Congo red adsorbent. Graphical abstract: Highlights: Porous NiCo2 O4 nanosheets have been fabricated by a facile hydrothermal method. The composite exhibited excellent adsorptive removal capacity toward Congo red. The adsorption may be the formation of ionic boding.